The intellectual competency in the system of the student's personality qualities: the experiental research - A P Lobanov (Peoples' Friendship University of Russia (RUDN University), 2010)
The article considers the systems analysis of the intellectual competency in higher education system. The competency is viewed as a factor of professionalism of a psychologist.